2005
DOI: 10.1002/bsl.678
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy in women: a review of its clinical usefulness for assessing risk for aggression and criminality

Abstract: Despite a flurry of studies examining psychopathy in women, and the recent release of the second version of the Hare Psychopathy Checklist--Revised manual, there is still little consensus whether the lateral extension of the current conceptualization of psychopathy to women is appropriate. In particular, very little agreement exists concerning the clinical utility of the Hare psychopathy measures to assess women's risk of future offending and violence. This article presents a comprehensive review of studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
53
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 67 publications
4
53
0
1
Order By: Relevance
“…Further, consistent with previous research (Nicholls, Ogloff, Brink, & Spidel, 2005), our analyses revealed higher mean values of psychopathic personality (i.e., CPS total score) in males than in females, based on both caregiver ratings and youth-self reports, thus indicating that these traits are more prevalent among males than females. However, no differences in the magnitude in genetic and environmental variance components were found across males and females.…”
Section: Discussionsupporting
confidence: 91%
“…Further, consistent with previous research (Nicholls, Ogloff, Brink, & Spidel, 2005), our analyses revealed higher mean values of psychopathic personality (i.e., CPS total score) in males than in females, based on both caregiver ratings and youth-self reports, thus indicating that these traits are more prevalent among males than females. However, no differences in the magnitude in genetic and environmental variance components were found across males and females.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the PCL-R is assumed to have relevance, for instance, in violence risk assessment in both women and men (Nicholls, Ogloff, Brink, & Spidel, 2005). However, concerns have been expressed about whether the PCL-R captures the construct of psychopathy satisfactorily in women (McKeown, 2010;Logan & Weizmann-Henelius, 2012).…”
mentioning
confidence: 99%
“…Thus, evidence suggests that psychopathy may be expressed differently amongst female offenders in comparison to their male counterparts (Forouzan & Cooke, 2005;Hamburger, Lilienfeld, & Hogben, 1996;Nicholls, Ogloff, Brink, & Spidel, 2005;Sevecke, Lehmkuhl, & Krischer, 2009;Vitale, Smith, Brinkley, & Newman, 2002). Finally, investigations to explore gender differences with regards to sexual aggression in psychopathic non-offenders are seemingly non-existent.…”
mentioning
confidence: 99%